The serine threonine kinase RIP3: lost and found - Morgan, Michael J. (BMB Rep, 2015)
Receptor-interacting protein kinase-3 (RIP3, or RIPK3) is an essential protein in the “programmed”, or “regulated” necrosis cell death pathway that is activated in response to death receptor ligands and other types of cellular stress. Programmed necrotic cell death is distinguished from its apoptotic counterpart in that it is not characterized by the activation of caspases; unlike apoptosis, programmed necrosis results in plasma membrane rupture, thus spilling the contents of the cell and triggering the activation of the immune system and inflammation. Here we discuss findings, including our own recent data, which show that RIP3 protein expression is absent in many cancer cell lines. The recent data suggests that the lack of RIP3 expression in a majority of these deficient cell lines is due to methylation-dependent silencing, which limits the responses of these cells to pro-necrotic stimuli. Importantly, RIP3 expression may be restored in many cancer cells through the use of hypomethylating agents, such as decitabine. The potential implications of loss of RIP3 expression in cancer are explored, along with possible consequences for chemotherapeutic response. [BMB Reports 2015; 48(6): 303-312]